Reexamination of the Import Structure of India: Reply - Dutta, M. (The Review of Economics and Statistics, 1976)
and the less-developed countries. Tower's alternate explanation that A does not differ systematically while (er/f) does is not very appealing. The empirical evidence (p. 453) suggests that r is an external cost and does not vary significantly from nation to nation. Given this, the less-developed countries would have to weight e relatively twice as large as the advanced nations to explain the typical disparity in the estimates of A between the two groups.